PENGUMPULAN BUDAYA LOKAL DENGAN ISLAM DI BAUBAU - Idham Idham (Pascasarjana IAIN Ambon, 2021)
This research is related to the traditions of Haroa Maludu and Ganda Maludu in Baubau and examined from the aspect of the struggle of local culture with Islam. This type of research is qualitative in nature by knowing the implementation of Ganda Maludu related to the Haroa Maludu method. The data collection is done by interview, observation, study documentation and recording. This study found that the local Indonesian culture outside that came with the local culture, there was a compromise between local culture and immigrant culture, there was attraction, there was a process of rejection and acceptance, there was a dynamic acculturation-accommodation and assimilation process and there was a struggle between the two. The culture is Haroa Maludu with the musical accompaniment of Ganda Maludu in Baubau. Haroa Maludu is a way of commemorating the birthday of the Prophet Muhammad, which is typical of Baubau. The findings of this study indicate that the Haroa Maludu ritual tradition in Baubau is divided into three cultural styles, namely 1) Gorona Puta, 2) Haroana Mia Bari, and 3) Maluduana Hukumu.